Review of medication therapy management provided by pharmacists to hypertension and diabetes patients in Indonesia - Nurswardiana, Hanna; Mulyani, Yani; Patonah, Patonah (Institute of Computer Science (IOCS), 2024)
Non-communicable diseases (NCDs) cause around 74% of deaths in the world, two of which are caused by hypertension and diabetes, which are chronic diseases. In general, it is characterized by high morbidity, polypharmacy and long-term treatment. This causes poor treatment compliance in the majority of respondents and has an impact on increasing disease complications, morbidity, mortality and treatment costs. Pharmacist intervention in managing NCDs has developed through a systematic, comprehensive medication management model approach such as the Medication Therapy Management (MTM) approach. This MTM model is designed to improve clinical outcomes from therapy, increase appropriate drug use, resolve treatment-related problems, improve respondents' quality of life and can provide good efficiency in avoiding risk factors for disease complications. This review was prepared to serve as comprehensive reference material regarding PTM. The method used is collecting scientific articles from national and international sources. The results obtained show that the MTM approach is an excellent pharmacist practice model in providing comprehensive pharmaceutical services for NCDs, especially hypertension and diabetes. The interventions that pharmacists can provide are comprehensive counseling by evaluating clinical results, compliance, knowledge, quality of life, perception of illness.